Network Pharmacology-Based Identification of Key Mechanisms of Xihuang Pill in the Treatment of Triple-Negative Breast Cancer Stem Cells - Yu-Zhu Zhang; Yu-Zhu Zhang; Jia-Yao Yang; Rui-Xian Wu; Chen Fang; Hai Lu; Hua-Chao Li; Dong-Mei Li; Hua-Li Zuo; Hua-Li Zuo; Hua-Li Zuo; Li-Ping Ren; et al. (Frontiers Media S.A., 2021)
Xihuang pill, an approved Chinese medicine formula (state medical permit number. Z11020073), is a commonly used adjuvant drug for cancer patients in China. Xihuang pill has a satisfactory effect in treating breast cancer in clinics, especially triple-negative breast cancer (TNBC), which is the most aggressive type of breast cancer, and finite effective therapies. However, the mechanism of Xihuang pill in treating TNBC remains unclear. The present study aims to explore the pharmacological mechanism of Xihuang pill in treating advanced TNBC. We identified the main chemical components of Xihuang pill by using HPLC-Q-TOF-MS/MS. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) analysis shows that serum containing Xihuang pill (XS) had no obvious killing effect on any subtype of breast cancer cells, but it inhibited mammosphere colony formation of two TNBC cell lines (4T1 and HCC1806 cells) and could enhance the inhibitory effect of paclitaxel (PTX) on the proliferation of 4T1 and HCC1806 cells when combined with PTX. Seventy-six active compounds in Xihuang pill, their 300 protein targets, and 16667 TNBC stem cell-related genes were identified. The drug-herb-active compound-target gene-disease network and enrichment analyses were constructed with 190 overlapping candidate targets. Through text mining and molecular docking, the target gene NR3C2 and its active compound naringenin were selected for further validation. According to the TCGA database, we observed that a high expression of NR3C2 promoted a higher survival probability regarding overall survival (OS). In vitro experiments indicated that naringenin presented an identical effect to XS, possibly by regulating the NR3C2 expression. Overall, this study explored the effect of Xihuang pill in treating advanced TNBC cells and showed that naringenin, which is the key active compound of Xihuang pill, could lessen the stemness of TNBC cells to produce a synergistic effect on PTX by regulating the NR3C2 gene.